National Bronchiolitis Hospitalization Rates Among Preterm and Full Term Infants: 2010–2015. (4th October 2017) - Krilov, Leonard R; Fergie, Jaime; Goldstein, Mitchell; McLaurin, Kimmie K; Wade, Sally; Diakun, David; Kong, Amanda
Abstract: Background: The 2014 American Academy of Pediatrics (AAP) policy statement on respiratory syncytial virus immunoprophylaxis (RSV IP) recommended against its use in infants 29–34 weeks gestational age (wGA) without chronic lung disease or bronchopulmonary dysplasia (CLD/BPD) or congenital heart disease (CHD). This study examined the impact of these changes by evaluating RSV IP use and bronchiolitis hospitalization rates among full-term (FT) and preterm (PT) infants 29–34 wGA in the 2014–15 RSV season relative to previous seasons. Methods: Infants born 7/1/2009 to 6/30/2015 were identified in the MarketScan Multistate Medicaid (MED) and Commercial (COM) databases; DRG and ICD-9-CM codes were used to select FT and PT infants without CLD/BPD or CHD. Outpatient RSV IP use was identified by drug and administration codes. Bronchiolitis hospitalizations were identified by diagnosis codes (466.11 and 466.19) during the RSV season (Nov–Mar) and summarized by chronologic age (CA). Hospitalization rates were calculated per 100 infant-seasons, and statistical significance was tested using generalized linear regression models with Poisson error, log link, and log offset for exposure time. Results: 1.1 mil MED and 1.0 mil COM births were identified; 5.2% MED and 4.8% COM infants were born at 29–34 wGA. RSV IP use decreased among MED and COM infants 29–34 wGA ( P < .01) in 2014–15 compared with 2013–14. Bronchiolitis hospitalization rates increased for MED and COM infants 29–34 wGA in 2014–15 compared with 2013–14 (rate ratios <3 months CA: MED 1.45, P = .009 and COM 2.1, P = .004; 3–6 months CA: MED 1.35, P = .023 and COM 1.7, P = .053), whereas the rates for FT infants remained the same (rate ratios 0.94–1.08, P > .05). Absolute increases were greatest for infants 29–30 wGA and <3 months CA (MED +10.0 and COM +8.3 per 100 infant-seasons). Similar trends were observed when 2014–15 was compared with the combined 2010–14 RSV seasons. Conclusion: In the 2014–15 RSV season, there was an increase in bronchiolitis hospitalization rates among PT infants born at 29–34 wGA when <3 months and 3–6 months CA, but no increase among FT infants. Trends were consistent in the MED and COM populations and are associated with the change to AAP policy. Funding: AstraZeneca Disclosures: L. R. Krilov, AstraZeneca/MedImmune: Consultant, Research grant and Research support; J. Fergie, MedImmune: Speaker's Bureau, Research grant and Research support; M. Goldstein, AstraZeneca/MedImmune: Consultant, Research grant and Research support; K. K. McLaurin, AstraZeneca: Employee, Salary; S. Wade, Truven Health Analytics: Consultant, Consulting fee; D. Diakun, Truven Health Analytics: Employee, Salary; A. Kong, Truven Health Analytics: Employee, Salary